2012
DOI: 10.1037/a0028687
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parenting on gay male couples' relationships, sexuality, and HIV risk.

Abstract: Parenthood changes couples' relationships across multiple domains, generally decreasing relationship quality, sexual satisfaction, and sexual frequency. Emerging research suggests that gay couples who are parenting might experience similar challenges. However, such changes might have even more profound implications for gay couples' health, and in particular their HIV risk, given the somewhat different ways in which they negotiate and tolerate sexual behaviors with outside partners. We aimed to examine these is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Research on changes in sexual desire and/or erectile function among fathers across the perinatal period is more limited, with most work documenting his reactions to his partner's changes in sexual desire (e.g., Schlagintweit et al, 2016). Similarly, the vast majority of studies examining changes in the sexual relationship among couples transitioning into parenthood have investigated mixedsex (male/female) couples; the few studies of same-sex couples have largely found patterns that parallel that of mixed-sex couples, with significant declines in sexual activity (Goldberg et al, 2010;Huebner et al, 2012) and sexual function (van Anders et al, 2013) in the initial postpartum/post-adoption period.…”
Section: Introductionmentioning
confidence: 99%
“…Research on changes in sexual desire and/or erectile function among fathers across the perinatal period is more limited, with most work documenting his reactions to his partner's changes in sexual desire (e.g., Schlagintweit et al, 2016). Similarly, the vast majority of studies examining changes in the sexual relationship among couples transitioning into parenthood have investigated mixedsex (male/female) couples; the few studies of same-sex couples have largely found patterns that parallel that of mixed-sex couples, with significant declines in sexual activity (Goldberg et al, 2010;Huebner et al, 2012) and sexual function (van Anders et al, 2013) in the initial postpartum/post-adoption period.…”
Section: Introductionmentioning
confidence: 99%
“…To be eligible for the parent project, both partners must have reported each other as their primary partner, defined as “someone to whom you feel committed above anyone else and with whom you have had a sexual relationship.” At least one partner in each couple was HIV-positive and on an acknowledged ART regimen for at least 30 days. In addition, participants were: (1) at least 18 years old; (2) born male and currently identified as male; (3) English speaking; and (4) able to provide informed consent. Between January 2009 and September 2012, surveys were administered with a combination of Computer Assisted Personal Interviewing (CAPI) and Audio Computer Assisted Self Interviewing (ACASI) procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have increasingly noted the diffi culty of individual-level HIV prevention interventions, and called for research that examines the social, relational and structural contexts of people's lives that sustain risk behavior or promote optimal health behaviors (Beyrer et al, 2012 ;Huebner, Mandic, Mackaronis, Beougher, & Hoff, 2012 ). As a large proportion of HIV risk behavior occurs within the context of a primary romantic relationship (Davidovich et al, 2001 ;Dolcini, Coates, Catania, Kegeles, & Hauck, 1995 ;Marin, Tschann, Gomez, & Kegeles, 1993 ;McCoy & Inciardi, 1993 ;Reilly & Woo, 2004 ;Sullivan, Salazar, Buchbinder, & Sanchez, 2009 ;Weinhardt et al, 2004 ), researchers have sought to examine how relationship dynamics contribute to risk behaviors, both within and outside the primary partnership among same-sex male couples Mitchell, Harvey, Champeau, & Seal, 2012 ;Prestage et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%